Upbringing as preparation to life or as life itself? The question is still open - Lidia MARSZAŁEK (Pavlo Tychyna Uman State Pedagogical University, 2014)
У статті проаналізовано значення дитинства у контексті всього розвитку людини. Життя дитини проходить у певний період часу, у будь-який момент. Сьогодення, з точки зору дитини, є найважливішою перспективою - світ існує «тут і зараз», і діти знайомляться з ним у цей час. Вони дізнаються як розуміти світ, формують власну точку зору на речі, створюють таку версію світу, де вони можуть знайти своє місце. Діти завжди випробовують речі, які відбуваються «зараз», і «я» - завжди в центрі. Діти вчаться через досвід, тому вони не можуть бути готові до життя, не маючи можливості брати участь в цьому житті. Діти є співавторами власного дитинства і суспільства, і, як наслідок, у дорослих є деякі серйозні завдання до виконання - окрім виховання і навчання - вони повинні дбати про збереження дитячого життєвого простору і всіх його якостей. В статье проанализировано значение детства в контексте всего развития человека. Жизнь ребенка проходит в определенный период времени, в любой момент. Настоящее, с точки зрения ребенка, является важнейшей перспективой. - Мир существует «здесь и сейчас», и дети знакомятся с ним в это время. Они узнают как понимать мир, формируют собственную точку зрения на вещи, создают такую версию мира, где они могут найти свое место. Дети всегда испытывают вещи, которые происходят «сейчас», и «я» - всегда в центре. Дети учатся через опыт, поэтому они не могут быть готовы к жизни, не имея возможности участвовать в этой жизни. Дети являются соавторами собственного детства и общества, и, как следствие, у взрослых есть некоторые серьезные задачи к выполнению - кроме воспитания и обучения - они должны заботиться о сохранении детского жизненного пространства и всех его качеств. The article presents childhood as a life period which is related to a quality of upbringing. Upbringing, in its turn is shown not only as a child's need, but as the child's right. As a result upbringing is not something understood as planned influence on a pupil's development in order to transform his/her personality towards an accepted educational perfection. The present notion of upbringing is characterized in different categories, most of them dealing with interaction. In the article upbringing is understood as a process which is a preparation to life - in different time perspectives, but it is still a vision of pupils' future, guiding them in order to achieve new and higher levels of development. This way of understanding can result in the conclusions that people are always «an unfinished» being, there are no limits to their development, they can improve themselves any time, and they can achieve transgression beyond their present existence. However, it can also be a source for an opinion that they are always - especially during childhood - an imperfect and immature being who needs to be shaped, completed with some knowledge, formed towards specific educational ideals and who needs to have some values implemented. The pedagogical vision, depicted in this way, must aim at discovering in children the things that are best and probably present in every sphere of their functioning - physical, psychological, social and spiritual ones. Children are co-authors of their own childhood and society, and as a consequence, adults have some serious tasks to fulfil - besides upbringing and teaching - they have to take care of preservation of children's life space and all its qualities. For this reason, tutors are expected to respect the right to experience childhood in its natural form and with its special character as it is, on one hand - a special moratorium on being a mature, efficient and competent man, and on the other hand - the period which is characterised by exceptionally beautiful existence. In the presence of these axioms, there can be only one answer to E. Claparedé's question - upbringing is the life which prepares to life.